Al-Quran Based on the Local Culture Learning â€œNggahi Mbojoâ€ For TPQ Students in Pajo District, Dompu Regency - Arifin Arifin; Indah Afrianti; Asmedy Asmedy; Enung Nurhasanah (Indonesian Journal of Elementary Education and Teaching Innovation, 2025)
The objective of this study is to ascertain the local culture-based Quran learning method known as 'Nggahi Mbojo' for TPQ students in Pajo Sub-district, Dompu Regency. The present study employs a mixed-methods research approach, utilising a combination of observational studies, questionnaires, documentation analysis, and direct interviews. The collected data is then subjected to rigorous analysis employing two primary approaches. Firstly, qualitative analysis was employed, encompassing data reduction, narrative presentation, and conclusion drawing based on patterns that emerged from interviews and observations. Secondly, quantitative analysis was utilised, encompassing the processing of questionnaire data to generate numerical values or scores, which were then presented in tabular, graphical, or descriptive statistical formats. The findings of the data analysis demonstrate the efficacy of local culture-based Qur'an learning 'Nggahi Mbojo' as a support for the learning process of reading the Qur'an for students at TPQ in Pajo sub-district, Dompu district. The integration of Qur'an learning with local culture-based learning in Nggahi Mbojo has been found to be a highly engaging subject, as evidenced by the results of the questionnaire, which revealed that 30 respondents strongly agreed (50.84%), while 20 respondents expressed agreement (33.89%). These results are further substantiated by internal factors, namely the motivation and enthusiasm of TPQ students, who have been encouraged to utilise local languages in Qur'an learning. The integration of Nggahi Mbojo has been found to enhance the interest and participation of students in the learning process of the Qur'an at TPQ. It has been observed that students' proficiency in reading the Qur'an is found to be deficient; however, by the integration of local culture into the Qur'an learning process, as exemplified by Nggahi Mbojo, serves to enhance students' motivation, given the ease with which they can comprehend the lessons delivered in their local language.